PEMANFAATAN SPYWARE BERBASIS CLIENT-SERVER UNTUK MONITORING AKTIVITAS KEYBOARD - Mulki Indana Zulfa (Universitas Islam Nahdlatul Ulama Jepara, 2015)
Supervision toward the use of information technology is indispensable due to the development of knowledge about the manufacture of virus, worm, or spyware. Installing antivirus is a solution to prevent the virus from contaminating the network or computer system. Nevertheless antivirus cannot monitor a user activity, in other word, keyboard activity. Keylogger software is capable of recording all keyboard activity. Keylogger must be installed on the target computer to record the activity of the keyboard. Then to take the logs files, the keylogger must have physical access to the computer. This would be a problem if the target computer to be monitored quite a lot. Methods of control keylogger spy agent with client-server mechanism that spyware technology become solution of these problems. Spy agent, as spyware client, will actively record keyboard activity of a person. The log file generated will be stored in a certain place so it will not arouse suspicion and users do not need to have physical access to retrieve log files. Control keylogger, as spyware server, can call spy agent to retrieve log files. The log files which can be retrieved will be stored on the server computer. Finally, the results of testing five computers become a target of all spy agent to provide the log file to control keylog. Keywords : keylogger, control keylogger-spy agent, client-server, keyboard activity, spyware. Pengawasan terhadap penggunaan teknologi informasi sangat diperlukan dikarenakan perkembangan ilmu tentang pembuatan virus, worm, atau spyware. Memasang antivirus merupakan solusi untuk mencegah virus mencemari jaringan atau sistem komputer. Meskipun demikian antivirus tidak bisa memantau aktivitas pengguna contohnya aktivitas keyboard. Keylogger merupakan perangkat lunak yang mampu merekam segala aktivitas keyboard. Keylogger harus diinstal terhadap target komputer yang akan direkam aktivitas keyboard-nya. Kemudian untuk mengambil file lognya, pengguna keylogger harus mempunyai akses fisik ke komputer tersebut. Hal ini akan menjadi masalah jika komputer target yang akan dipantau cukup banyak. Metode control keylogger-spy agent dengan mekanisme client-server yang teknologi spyware menjadi solusi dari masalah tersebut. Spy agent, sebagai spyware client, akan secara aktif merekam aktivitas keyboard seseorang. File log yang dihasilkan akan disimpan di tempat tertentu sehingga tidak akan menimbulkan kecurigaan pengguna dan tidak perlu mempunyai akses fisik untuk mengambil file log. Control keylogger, sebagai spyware server, dapat menghubungi spy agent untuk mengambil file log. File log yang berhasil diambil akan disimpan dengan baik di komputer server. Akhirnya, dari hasil pengujian lima komputer yang dijadikan target spy agent semuanya dapat memberikan file log kepada control keylog. Kata kunci: keylogger, control keylogger-spy agent, client-server, aktivitas keyboard, spyware.